RESPON VARIETAS KACANG TANAH (Arachis hypogaea L.) TERHADAP PERLAKUAN PUPUK KANDANG SAPI - Rinny Agri Surya; Widodo Haryoko; M. Zulman Harja Utama (Universitas Muara Bungo, 2019)
This study aims to determine the effect of interactions between peanut varieties and treatment of cow dung. This research was conducted in Kalumbuk Village, Padang City, West Sumatra from September to December 2018. The study was conducted using Factorial Completely Randomized Design. The experimental treatment consisted of two factors. The first factor consisted of 3 peanut varieties, namely varieties of Talam 1, Takar 2 and Tala 1. The second factor was cow dung which consisted of 4 levels namely 0 tons ha-1, 5 tons ha-1, 10 tons ha-1 and 15 ton ha-1. The combination of each treatment obtained 9 units with replications 3 times. The parameters observed were plant height, number of primary branches, number of nodules, age of flower appearance, number of pods, percentage of soft pods, weight of pods per clump, number of seeds, weight of 100 seeds, dry pod weight per plot and per hectare. The results showed that the interaction of peanut varieties with cow manure treatment on the parameters of the number of nodules and the production of the weight of dry pods per hectare was highest, namely in the Talam 1 variety with 15 tons ha-1 cow dung. Keywords: Cow Manure, Peanut Varieties